Occipital Nerve Blockage in Cervicogenic Headache: A case Report and Brief Review of Literature - Tuba Tulay Koca (Medicine Science, 2015)
Head and neck pains are frequently encountered complaints in physical therapy outpatient clinics. In most clinics worldwide, nerve blockage technique is successfully used together with pharmacological treatments. Trigger point blockage, occipital nerve blockage, trigeminal nerve blockage, and C2-3 spinal nerve blockage are all effective in the treatment of all types of headaches. Peripheral nerve blockages have long been used in the treatment of headaches. Peripheral nerve blockages may include the major and minor occipital, supraorbital, supratrochlear, trigeminal, auriculotemporal and glossopharyngeal nerves. Additionally there is no significant consensus on peripheral nerve blockage techniques applied to primary or secondary headaches. Occipital nerve blockage is an easy, reliable, practical method such other peripheral nerve blockages. Here, we present a 64-year old male with head and neck pain diagnosed as cervical spondylosis and treated with occipital nerve and trigger point blockage. [Med-Science 2015; 4(1.000): 1972-8]